BCL11A Is Oncogenic and Predicts Poor Outcomes in Natural Killer/T-Cell Lymphoma - Shi, Hongyun; Li, Chun; Feng, Wei; Yue, Jianjun; Song, Jingfang; Peng, Aizhi; Wang, Hua (Frontiers in Pharmacology, 2020)
The current treatment for natural killer /T-cell lymphoma (NKTL) among advanced/relapsed patients is unsatisfying, thereby highlighting the need for novel therapeutic targets. B‐cell chronic lymphocytic leukemia/lymphoma 11 A (BCL11A), as a transcription factor, is oncogenic in several neoplasms. However, its function in NKTL remains unclear. Quantitative real-time polymerase chain reaction and western blot analysis were used to measure the BCL11A expression levels among NKTL patients and in NKTL cell lines. Natural killer (NK) cells from healthy subjects were used as negative control. Transient transfection with small interfering RNA was used to knockdown the expression in NKTL cell lines. Samples and clinical histories were collected from 343 NKTL patients (divided into test and validation groups) to evaluate the clinical value of BCL11A expression level. The BCL11A expression was upregulated among NKTL patients and in NKTL cell lines. Reduced cell proliferation and increased apoptosis were observed after silencing BCL11A in NKTL cell lines. BCL11A expression level was correlated with RUNX3, c-MYC, and P53 in NKTL. Notably, a high BCL11A expression was correlated with unfavorable clinical characteristics and predicted poor outcomes in NKTL. In conclusion, BCL11A was overexpressed in NKTL, while its upregulation promoted tumor development. Therefore, BCL11A expression level may be a promising prognostic biomarker for NKTL.